Prospective Two-Center Comparison of Three Chromogenic Agars for Methicillin-Resistant Staphylococcus aureus Screening in Hospitalized Patients - Dodémont, Magali (J Clin Microbiol, 2015)
Three chromogenic media, chromID MRSA SMART (SMART), chromID MRSA first generation (chromID), and Brilliance MRSA (OX2), were evaluated for methicillin-resistant Staphylococcus aureus (MRSA) screening using 1,220 samples. The sensitivity at 24 h was significantly better with the SMART agar (66.4%) than that with chromID agar (50.5%). Enrichment and incubation until 48 h are still needed for an optimal yield.